Building Europe. A History of European Unification - Loth, Wilfried (De Gruyter, 2015)
Relying on internal sources, Wilfried Loth analyses the birth and subsequent development of the European Union, from the launch of the Council of Europe and the Schuman Declaration until the Euro crisis and the contested European presidential election of Jean-Claude Juncker. This book shines a light on the crises of the European integration, such as the failure of the European Defence Community, De Gaulle`s empty chair policy, or the rejection of the European Constitution in France and the Netherlands, but also highlights the indubitable successes that are the Franco-German reconciliation, the establishment of the European common market, and the establishment of an expanding common currency. What this study accomplishes, for the first time, is to illuminate the driving forces behind the European integration process and how it changed European politics and society.An enlightening work. Arequired reading for all who doubt the unfinished history of Europe. &#8211 Rolf Steininger, Frankfurter Allgemeine Zeitung.This book will become an indispensable standard work. &#8211 Jörg Himmelreich, Neue Zürcher Zeitung.